2014
DOI: 10.1371/journal.pone.0090446
|View full text |Cite
|
Sign up to set email alerts
|

Hemokinin-1(4-11)-Induced Analgesia Selectively Up-Regulates δ-Opioid Receptor Expression in Mice

Abstract: Our previous studies have shown that an active fragment of human tachykinins (hHK-1(4-11)) produced an opioid-independent analgesia after intracerebroventricular (i.c.v.) injection in mice, which has been markedly enhanced by a δ OR antagonist, naltrindole hydrochloride (NTI). In this study, we have further characterized the in vivo analgesia after i.c.v. injection of hHK-1(4-11) in mouse model. Our qRT-PCR results showed that the mRNA levels of several ligands and receptors (e.g. PPT-A, PPT-C, KOR, PDYN and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The total RNA was extracted from the tibial bone marrow cells using TRlzol Reagent (Invitrogen Corp., Carlsbad, California, USA) according to the manufacturer’s instructions. Two µg of total RNA in each group was reverse transcribed into cDNA in a final volume of 50 µl as in previous reports ( Fu et al, 2014 ; Zhang et al, 2014 ). The gene of GAPDH was selected as an endogemous internal control gene and a non-template reaction was included as negative control for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The total RNA was extracted from the tibial bone marrow cells using TRlzol Reagent (Invitrogen Corp., Carlsbad, California, USA) according to the manufacturer’s instructions. Two µg of total RNA in each group was reverse transcribed into cDNA in a final volume of 50 µl as in previous reports ( Fu et al, 2014 ; Zhang et al, 2014 ). The gene of GAPDH was selected as an endogemous internal control gene and a non-template reaction was included as negative control for each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…HK-1 had a pronociceptive effect after intrathecal or intracerebroventricular administration, causing pain and scratching behavior without influencing the withdrawal latency to a noxious heat stimulus [34,43]. However, in other studies, an analgesic effect was shown upon intracerebroventricular injection [44][45][46]. Its potential contribution to pain sensitization was shown by the upregulation of Tac4 mRNA expression in lipopolysaccharide-stimulated cultured microglia [47], and in the rat spinal dorsal horn after complete Freund's adjuvant (CFA)-induced paw inflammation [48].…”
Section: Introductionmentioning
confidence: 93%
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot analysis were then performed as described previously, with minor modifications. 32 A total of 50 μg of protein from each sample was resolved by sodium dodecyl sulfate polyacrylamide gel electrophoresis, transferred onto polyvinylidene fluoride membranes (Roche, Indianapolis, IN, USA) by electroblotting, and probed with specific primary antibodies, including monoclonal mouse anti-p-FAK (1:1,000, Santa Cruz Biotechnology, Santa Cruz, CA, USA), monoclonal mouse anti-human vitronectin (1:1,000, R&D Systems), monoclonal mouse anti-human Bcl-2 (1:500, Santa Cruz Biotechnology), monoclonal mouse anti-human Bax (1:500, Santa Cruz Biotechnology, and monoclonal mouse anti-human caspase-3 (1:1,000, R&D Systems). The primary antibodies were detected using horseradish peroxidase-conjugated goat anti-mouse IgG (1:5,000, Promega, Heidelberg, Germany) in blocking solution.…”
Section: Western Blot Assaymentioning
confidence: 99%